2020
DOI: 10.1021/acs.biochem.0c00267
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigation of Cysteamine Dioxygenase

Abstract: Thiol dioxygenases are mononuclear non-heme Fe II -dependent metalloenzymes that initiate the oxidative catabolism of thiol-containing substrates to their respective sulfinates. Cysteine dioxygenase (CDO), the best characterized mammalian thiol dioxygenase, contains a three-histidine (3-His) coordination environment rather than the 2-His-1-carboxylate facial triad seen in most mononuclear non-heme Fe II enzymes. A similar 3-His active site is found in the bacterial thiol dioxygenase 3-mercaptopropionate dioxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 44 publications
(101 reference statements)
1
33
1
Order By: Relevance
“…The arc consists of several underlying peaks with similar anisotropic hyperfine couplings. There are two additional sets of peaks with frequencies of ( 6 , 7 , 8 , 9 ) MHz; these are more weakly coupled 1 H as they appear closer to the 1 H Larmor frequency along the diagonal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The arc consists of several underlying peaks with similar anisotropic hyperfine couplings. There are two additional sets of peaks with frequencies of ( 6 , 7 , 8 , 9 ) MHz; these are more weakly coupled 1 H as they appear closer to the 1 H Larmor frequency along the diagonal.…”
Section: Resultsmentioning
confidence: 99%
“…Thiol dioxygenases are a subset of nonheme mononuclear iron oxygenases that catalyze the O 2 -dependent oxidation of thiol-bearing substrates to yield the corresponding sulfinic acid. Among this group, cysteine dioxygenase (CDO) ( 1 , 2 , 3 , 4 , 5 ) and cysteamine dioxygenase (ADO) ( 6 , 7 ) are responsible for the biosynthesis of cysteine sulfinic acid (CSA) and hypotaurine (HT), respectively, which are precursors for the biosynthesis of taurine ( 1 ). Among bacteria, a number of other thiol dioxygenases have been identified, including mercaptosuccinate dioxygenase (MSDO) ( 8 ) and 3-mercaptopropionate dioxygenase (3MDO) ( 9 , 10 , 11 , 12 , 13 , 14 ).…”
mentioning
confidence: 99%
“…The precise role of the alternative triad in NCOs is not yet clear, but an Asp176Asn variant in AtPCO4 resulted in near-ablated activity. If, as reported for ADO, substrate coordination of NCOs is monodentate to the active site metal [38], it is possible that the conserved Asp in the NCO form of this triad could play a role in binding the N-terminal amine of their polypeptide substrates.…”
Section: Two Sub-classes Of Thiol Dioxygenasementioning
confidence: 82%
“…It is also possible that ADO shares another structural feature with CDO: in 2018, Wang et al published evidence that a Cys-Tyr crosslink can occur in ADO between Cys 220 and Tyr 222 [37]. Interestingly, recent spectroscopic investigations indicate that metal -substrate coordination in ADO is distinctive from that of CDO: While crystallographic evidence has shown these enzymes to bind their substrates in a bidentate manner, spectroscopic evidence has indicated that ADO binds cysteamine in a monodentate manner via the thiol but not via its amine group [38,39].…”
Section: Cysteamine Dioxygenasementioning
confidence: 99%
“…Additionally, ADO can readily form dinitrosyl iron complexes anaerobically in the presence of substrates (21). EPR and magnetic circular dichroism characterization of the Fe(III)-ADO by Brunold et al has led to a similar conclusion of the substrate-binding mode and a distinct secondary coordination sphere from CDO and MDO (24).…”
Section: Introductionmentioning
confidence: 96%